2017
DOI: 10.1007/s11207-017-1055-x
|View full text |Cite
|
Sign up to set email alerts
|

Spectro-Imaging Polarimetry of the Local Corona During Solar Eclipse

Abstract: Results are presented from spectro-imaging polarimetry of radiation from the local solar corona during the 2013 total solar eclipse in Gabon. This polarimetric observation was performed from 516.3 nm to 532.6 nm using a prototype Fiber Arrayed Solar Optical Telescope (FASOT). A polarimetric noise level on the order of 10 −3 results from a reduced polarimetric optical switching demodulation (RPOSD) procedure for data reduction. It is revealed that the modality of fractional linear polarization profiles of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
(15 reference statements)
0
9
0
3
Order By: Relevance
“…It has also been demonstrated that the Hanle effect, a process involving modification of polarization by magnetic fields, could be powerful to diagnose the weak magnetic fields in the upper solar atmosphere (e.g., Trujillo Bueno et al, 2002; Li H et al, 2017). All these techniques require a precise measurement of polarization of coronal emission lines (e.g., Qu ZQ et al, 2009, 2017). Thanks to the greatly reduced level of scattered light, the 2017 total solar eclipse provided an excellent opportunity for such a measurement.…”
mentioning
confidence: 99%
“…It has also been demonstrated that the Hanle effect, a process involving modification of polarization by magnetic fields, could be powerful to diagnose the weak magnetic fields in the upper solar atmosphere (e.g., Trujillo Bueno et al, 2002; Li H et al, 2017). All these techniques require a precise measurement of polarization of coronal emission lines (e.g., Qu ZQ et al, 2009, 2017). Thanks to the greatly reduced level of scattered light, the 2017 total solar eclipse provided an excellent opportunity for such a measurement.…”
mentioning
confidence: 99%
“…(3) 观测目标对仪器参数设计和谱线选择的约束. 这两束光同时测量构成偏振光学开光 [32,33] 操作的基 础. 对波片起始位置以及围绕主光轴转动角度进行优 化, 可以获得合理的偏振测量效率的分配 [56] .…”
Section: Compt的积分视场光谱测量(integral Fieldunclassified
“…对波片起始位置以及围绕主光轴转动角度进行优 化, 可以获得合理的偏振测量效率的分配 [56] . 为了提 高偏振测量灵敏度同时又要考虑不降低时间分辨率, 我们需要进行简化偏振光学开关操作 [33] . 特点可能对望远镜弯程产生的影响, 初步采用Serrur-ier桁架结构 [57] .…”
Section: Compt的积分视场光谱测量(integral Fieldunclassified
See 1 more Smart Citation
“…Due to the compact and symmetrical optics configuration of FASOT up to the polarization modulator, the additional polarization from instrument is minimized. On the other hand, a novel polarization demodulation technique named reduced optical switching demodulation [4] is adopted by FASOT to improve the polarimetric sensitivity and reduce the integration time. These technologies mentioned above will make FASOT obtain a polarimetric noise level on the order of 8.0 × 10 −4 .…”
Section: Introductionmentioning
confidence: 99%